Influence of Foundation Rigidity on the Structural Response of Mat Foundation - Sami W. Tabsh; Magdi El-Emam (Advances in Civil Engineering)
A mat is a type of shallow foundation that is appropriate for structures supported on soil having relatively low bearing capacity or excessive settlement. Structural analysis of a mat foundation can be accomplished by either assuming the mat to be perfectly rigid or by considering the soil-structure interaction. This study researches the relationship between the mat-soil rigidity and structural response in terms of the soil bearing pressure, bending moment, and shear within the mat. To accomplish the objective of the study, 70 different mats are analyzed using a linearly elastic finite element approach. The variables that are considered in the analysis are the number of bays in each direction, center-to-center column spacing, mat thickness, panel aspect ratio, column cross section dimensions, soil modulus of subgrade reaction, and modulus of elasticity of concrete. A dimensionless mat rigidity measure was developed that determines whether a given mat can be reasonably analyzed by assuming it to be infinitely rigid. The developed rigidity factor takes into consideration all parameters that significantly affect the mat structural response. Results of the analysis indicate that there is strong correlation between the developed rigidity factor and critical soil bearing pressure and maximum internal bending moment within the mat. No correlation was observed between the mat rigidity and critical shear force. Relationships between the rigidity factor and the critical soil bearing pressures and bending moments, relative to the response of the infinitely rigid mat, are proposed. A parametric study is included to demonstrate the impact of the variables that affect the rigidity index on the response of the mat.